The grammatical Error in the Italian Linguistic Landscapes of Buenos Aires: a Double Glottopolitics and Glottodidactics Perspective - Capelli, Francesca; Pitton Straface, Mariel Angeles (ItaliAMO: Promotion of Italian Studies in the Academic and Non-Academic Environment, 2023)
The public space of the city of Buenos Aires is dotted with Italian linguistic landscape (LL), a legacy of the migratory waves that occurred between the end of the 19th century and the beginning of the second post-war period. During one century and a half, the attitude towards Italians has gone from contempt to idealization. Even Italian LL has turned into distinctive signs of quality and refinement, but it is also a reservoir of linguistic variation which can be used to create low-cost language teaching material. This article proposes an analysis pattern for the linguistic variation present in the Italian LL in Buenos Aires and the use of this material as an authentic text for the elaboration of a didactic unit for students of Italian for foreigners.